Development of a Sprite-Based Architecture for Creating 2D Games in Reconfigurable Environments Using FPGA Devices - Alves, Gabriel Sá B.; Dias, Anfranserai M.; Sarinho, Victor T. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
The understanding of concepts worked on FPGAs combined with the creation of games in hardware platforms has helped in the understanding and assimilation of the necessary techniques and approaches to build digital game systems. This work presents the development and validation of a Sprite-Based Architecture that aims to develop 2D games in reconfigurable environments based on FPGA devices. To this end, a set of functions and other resources implemented in C language were develop, that aims to help the creation of games through the developed architecture.